1994
DOI: 10.1111/j.1651-2227.1994.tb13229.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen free radicals and antioxidants in cystic fibrosis: the concept of an oxidant‐antioxidant imbalance

Abstract: Patients with cystic fibrosis frequently exhibit increased oxygen free radical generation from activated neutrophils due to chronic lung inflammation on the one hand and antioxidant deficiencies due to exocrine pancreatic insufficiency on the other, resulting in an oxidant–antioxidant imbalance in favor of the former. As a consequence, free radical attack on unsaturated fatty acids of lipid structures leading to lipid peroxidation and damaging effects on proteins may occur. In the lung, antiproteases are thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
63
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 67 publications
5
63
0
1
Order By: Relevance
“…7 In this study, all patients were regularly supplemented with vitamin A and those with severe fibrosis or cirrhosis at biopsy had serum levels of retinol similar to those in matched control patients with CF without liver disease (data not shown). Lipid peroxidation might influence the development of liver disease, [42][43][44] but the patients with severe fibrosis or cirrhosis had serum levels of ␣-tocopherol within the normal reference interval and did not differ from patients with CF without liver disease (data not shown). Similar to other studies, we found no correlation among liver disease and lung function or bacterial colonization, implying that bacterial toxin production had no great impact on liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…7 In this study, all patients were regularly supplemented with vitamin A and those with severe fibrosis or cirrhosis at biopsy had serum levels of retinol similar to those in matched control patients with CF without liver disease (data not shown). Lipid peroxidation might influence the development of liver disease, [42][43][44] but the patients with severe fibrosis or cirrhosis had serum levels of ␣-tocopherol within the normal reference interval and did not differ from patients with CF without liver disease (data not shown). Similar to other studies, we found no correlation among liver disease and lung function or bacterial colonization, implying that bacterial toxin production had no great impact on liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation products e.g. malondialdehyde has been taken as a biomarker for oxidative stress in biological system [20,22] . This circumstance can lead to 'oxidative stress' i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Activated neutrophils and macrophages are major sources of oxygen free radicals including hydrogen peroxide (H 2 O 2 ). Indeed, lung infection in CF leads to increased oxygen free radical generation [7,8]. Furthermore, sputum of CF-patients has been shown to prime neutrophils towards enhanced release of oxygen radicals [9].…”
mentioning
confidence: 99%